Communicating and promoting financial services - Manton, Steve (Henry Stewart Talks, 2008)
A challenging environment, New issues and new marketing channels, The impact of online, Offline and online change, Relevance, Permanence, Key marketing issues, Marketing tactics, Online advertising market share up, The importance of online marketing for financial services, Maximizing online and offline marketing, Combining natural and paid marketing, Targeting and accountability, Measurability, The importance of online marketing